2020
DOI: 10.1038/s41590-020-0607-7
|View full text |Cite
|
Sign up to set email alerts
|

Developmental plasticity allows outside-in immune responses by resident memory T cells

Abstract: Central memory T (T CM ) cells patrol lymph nodes and perform conventional memory responses upon re-stimulation: proliferation, migration, and differentiation into diverse T cell subsets while also self-renewing. Resident memory T (T RM ) cells are parked within single organs, share properties with terminal effectors, and contribute to rapid host protection. We observed that reactivated T RM cells rejoined the circulating pool. Epigenetic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
253
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(279 citation statements)
references
References 57 publications
21
253
1
4
Order By: Relevance
“…Thus, defective TCR-mediated effector cytokine production could underlie the impaired protection against secondary influenza virus infection. Notably, T RM cells can undergo in situ proliferation and generate secondary effector T cells [41, 57, 58]. Previously, it has been shown that memory T cells in aged mice are senescent in proliferation during secondary expansion [8].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, defective TCR-mediated effector cytokine production could underlie the impaired protection against secondary influenza virus infection. Notably, T RM cells can undergo in situ proliferation and generate secondary effector T cells [41, 57, 58]. Previously, it has been shown that memory T cells in aged mice are senescent in proliferation during secondary expansion [8].…”
Section: Discussionmentioning
confidence: 99%
“…While the overall blood T cell population displayed a resting functional state, the host blood CD8+ T cell population displayed a strong enrichment of proliferating T cells according to the proportion of cells within the G2/M phase. It remains scarcely investigated whether and how TRM cells exit their tissue of origin 10,19. Based on our cell cycle analysis, we speculate that preceding T cell activation might have mobilized them out of their respective tissues.…”
Section: Although Insights Into the Regulation Of Human Tissue Residementioning
confidence: 91%
“…Lymphocytes are thought to display common features inherent to the tissue in which they reside 21,39,44,45,46 . Consequently, migrating immune cells must be able to readily adapt to their new environment at the transcriptional level, although the type and speed of tissue-imprinting will vary with the tissue and the immune cell of interest 20,39,45,46,47,48,49,50 . For instance, it was proposed that while Tregs from skin and colon retain a common Treg program, they concomitantly acquire tissue-specific profiles 21 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it was proposed that while Tregs from skin and colon retain a common Treg program, they concomitantly acquire tissue-specific profiles 21 . Conversely, studies characterizing TRM, which share several characteristics with IEL subsets, also observed a progressive acquisition of a tissue-specific transcriptional profile, distinct of circulating memory cells 46 .…”
Section: Discussionmentioning
confidence: 99%